Effect of the long-term application of organic matter on soil carbon accumulation and GHG emissions from a rice paddy field in a cool-temperate region, Japan. -I. Comparison of rice straw and rice straw compost -. Issue 1 (2nd January 2020) - Takakai, Fumiaki; Kominami, Yasuhiro; Ohno, Satoshi; Nagata, Osamu
ABSTRACT: The influence of the long-term combination of rice straw removal and rice straw compost application on methane (CH4 ) and nitrous oxide (N2 O) emissions and soil carbon accumulation in rice paddy fields was clarified. In each of the initial and continuous application fields (3 and 39−51 years, respectively), three plots with different applications of organic matter were established, namely, rice straw application (RS), rice straw compost application (SC) and no application (NA) plots, and soil carbon storage (0−15 cm), rice grain yield and CH4 and N2 O fluxes were measured for three years. The soil carbon sequestration rate by the organic matter application was higher in the SC plot than in the RS plot for both the initial and continuous application fields, and it was lower in the continuous application field than in the initial application field. The rice grain yield in the SC plot was significantly higher than those in the other plots in both the initial and continuous application fields. Cumulative CH4 emissions followed the order of the NA plot < the SC plot < the RS plot for both the initial and continuous application fields. The effect of the organic matter application on the N2 O emissions was not clear. In both the initial and continuous application fields, the increase in CH4 emission by the rice straw application exceeded the soil carbon sequestration rate, and the change in the net greenhouse gas (GHG) balance calculated by the difference between them was a positive, indicating a net increase in the GHG emissions. However, the change in the GHG balance by the rice straw compost application showed negative (mitigating GHG emissions) for the initial application field, whereas it showed positive for the continuous application field. Although the mitigation effect on the GHG emissions by the combination of the rice straw removal and rice straw compost application was reduced by 21% after 39 years long-term application, it is suggested that the combination treatment is a sustainable management that can mitigate GHG emissions and improve crop productivity.